Olhares cruzados no Projeto Lifelines - Imagens da educação na Floresta de Caxiuanã: uma vivência de criatividade e afeto - SANTOS, Janine Valente dos (2022)
Between 2016 and 2017, the connection between the Goeldi Museum and the Stepping Stones Museum For Children provided an educational experience that brought together students from the São Sebastião school in the Caxiuanã National Forest (Pará-Brazil), with American students from the Fairchild Wheeler School, of Connecticut-United States. Through images, the article documents the process of research and exchange among students. The study proposes a reflection on how the educational experience is transforming and works as a bridge and window to the world. The focus of the research is the students of São Sebastião who through the drawings could transpose their perceptions of the space in which they live and how they recognize in him. In analyzing this process we realized that the traditional knowledge allied to the contents proposed by the actions of the educational program of the Goeldi Museum in Caxiuanã enabled these students bases to unite science, art and the experience in their localities and to create elements that, besides valuing the culture strengthened their identities. The key point of the interaction process is creativity and affection.